1971
DOI: 10.1128/aem.21.3.476-481.1971
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella anatum Heated in Various Media

Abstract: Survival of Salmonella anatum heated at 55 C for 35 min was determined in solutions of various chemical constituents of foods including salts, carbohydrates, amino acids, peptides, nucleic acids, gums, and stabilizers and compared with survival in 0.1 M phosphate buffer (pH 7.0). Commercially sterilized whole milk gave the most protection against heat. Trypticase Soy Broth, various peptide mixtures, and some amino acids gave substantial protection. Results with carbohydrates were variable, with mannitol, sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The increased survival of Salmonella in low water activity environments has been mainly investigated with respect to the cells' ability to tolerate heat processing. The effect of food composition and structure on heat resistance of Salmonella has been well documented (Moats et al 1971;Ahmed et al 1995;Mattick et al 2001;Smith et al 2001), while it has been clearly demonstrated that a much more drastic heat treatment is required to destroy Salmonella in dried foods with low a w such as dried milk, corn flour, cocoa powder, egg powders and alfalfa seeds (McDonough and Hargrove 1968;VanCauwenberge et al 1981;Juven et al 1984;Jung and Bauchat 1999;Beuchat and Scouten 2002). Exposure of salmonellae to low a w could markedly reduce the effectiveness of a subsequent heat process.…”
Section: Discussionmentioning
confidence: 99%
“…The increased survival of Salmonella in low water activity environments has been mainly investigated with respect to the cells' ability to tolerate heat processing. The effect of food composition and structure on heat resistance of Salmonella has been well documented (Moats et al 1971;Ahmed et al 1995;Mattick et al 2001;Smith et al 2001), while it has been clearly demonstrated that a much more drastic heat treatment is required to destroy Salmonella in dried foods with low a w such as dried milk, corn flour, cocoa powder, egg powders and alfalfa seeds (McDonough and Hargrove 1968;VanCauwenberge et al 1981;Juven et al 1984;Jung and Bauchat 1999;Beuchat and Scouten 2002). Exposure of salmonellae to low a w could markedly reduce the effectiveness of a subsequent heat process.…”
Section: Discussionmentioning
confidence: 99%
“…In high a w foods, salts and sugars have been reported to protect bacteria by stabilizing the proteins and membranes (Timasheff and others 1976; Leslie and others 1995). The increased heat resistance of bacteria in the presence of lipids has been attributed to reduced a w of lipid systems and dehydration of cells immersed in the lipid phase (Ahmed and others 1995; Kaur and others 1998) while that in the presence of proteins has been attributed to the formation of aggregates of bacteria (Moats and others 1971). Caseins have been reported to protect more bacteria subjected to heat treatment when present in micellar form than in nonmicellar form (Black and others 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Polyols and sugars increase the heat resistance (reduce stress-induced injury and death) of bacteria (2,4,6,7,9,11,13,16), yeasts (6,9), and fungal spores (3,5) and reduce acid injury of staphylococci (15). When polyols or sugars are present in the heating menstruum, higher temperatures are required to effect a given killing or injury level (16).…”
mentioning
confidence: 99%